Hind- and Midfoot Motion After Ankle Arthrodesis. (December 2015) - van der Plaat, Laurens W.; van Engelen, Susanne J. P. M.; Wajer, Quirine E.; Hendrickx, Roel P. M.; Doets, Kees H. C.; Houdijk, Han; van Dijk, C. Niek
Background: After ankle arthrodesis (AA), compensatory increased range of motion in adjacent joints might lead to increased osteoarthritis. Evaluation of patient-reported outcomes after AA with validated questionnaires is rare. Likewise, reliable radiographic analysis of the position of the AA, expected to influence the range of motion of the hind- and midfoot, is lacking. Therefore, the current study was performed. Methods: Seventeen patients with unilateral AA were included. Sagittal hind- and midfoot range of motion was measured radiographically. The position of the AA in the sagittal and coronal planes and osteoarthritis of adjacent joints were also evaluated radiographically. Measurements were compared to the contralateral side. Patient-reported outcomes via validated questionnaires were compared to a control group (n = 18). Results: Average follow-up was 3.5 years. Mean combined hind- and midfoot sagittal range of motion after AA equaled that of the contralateral side (20.8 vs 21.0 degrees; P = .93). The tibiotalar angle after AA equaled that of the contralateral side (107 vs 107 degrees; P = .86). The talus was translated posteriorly after AA (T-T ratio 0.45 vs 0.34; P < .001). Low intraclass correlation coefficients (ICC) precluded reliable evaluation of the coronal position of the hindfoot (ICC, 0.07 and −0.34) and osteoarthritis in adjacent joints (ICC range, 0-0.54). SF-36 physical health scores after AA are lower as compared with those of controls (50 vs 56; P = .01). Scores on the Foot and Ankle Outcome Score and Ankle Osteoarthritis Scale were also significantly lower. Patient satisfaction with AA was high (average visual analog scale score, 83). Conclusion: No increased sagittal range of motion in the hind- and midfoot after AA was found at 3.5 years of follow-up as compared with the contralateral side. Tibiotalar angles were equal. The talus was translated posteriorly. The hindfoot alignment view was not suitable to analyze the position of the hindfoot. Low ICC of the Kellgren and Lawrence scale precluded evaluation of osteoarthritis of adjacent joints. Patients scored lower than controls on self-reported outcome questionnaires but were satisfied with the result of AA. Level of evidence: Level III, comparative series.